Contrasting Floristic Diversity of the Hengduan Mountains, the Himalayas and the Qinghai-Tibet Plateau Sensu Stricto in China - Yu, Haibin; Miao, Shenyu; Xie, Guowen; Guo, Xueying; Chen, Zhao; Favre, Adrien (Frontiers in Ecology and Evolution, 2020)
The Qinghai-Tibet Plateau sensu lato (QTP s.l.) harbors an exceptionally high biodiversity, especially at its southeastern margin: this area encompasses the Hengduan Mountains and the eastern Himalayas, which have been listed as biodiversity hotspots. To the contrary, the plateau interior (namely the Qinghai-Tibet Plateau sensu stricto, QTP s.s.) is relatively species-poor because of its particularly harsh climate. With contrasting geological histories and environmental conditions of the Hengduan Mountains, the Himalayas and the QTP s.s., it would be expected that floristic compositions and diversity patterns of these three regions would differ between each other. To compare the floristic diversity of these three regions, we assembled data on seed plant’s distribution in the three regions based on county-level mapping from published monographs and online databases, and we then analyzed their floristic features and species diversity patterns (horizontal and elevational). We found that the Hengduan Mountains hosted the most seed plant species (8,439), as expected. The highest percentage of shrub (22.88%) and tree species (9.80%) were in the Himalayas, whereas herbaceous species (81.50%) were relatively more prominent in the QTP s.s.. The Hengduan Mountains also had the most species-rich genera (10) with more than 50% of their total species diversity in China. Also, temperate genera dominated across these three regions, with a highest percentage (77.61%) within the QTP s.s.. Across the QTP s.l., species diversity gradually decreased from the southeastern part to the northwest, and most of seed plants were distributed in the southern and eastern margin of the Hengduan Mountains and East Himalayas. Along elevational gradients, species richness all demonstrated a hump-shape curve, but the most species-rich elevation zone differed for each type of life-form across the three regions. Our study sets a base for exploring the origin and evolution of mountain taxa, as well as provides a snapshot of the current plant distribution, which will certainly be modified by climate change.